Industrial relations in post-communism: Workplace co-operation in Hungary and Slovenia - Miroslav Stanojević (Journal for East European Management Studies, 2001)
The paper is derived from a survey conducted in the second half of 1999. According to the data, two different types of industrial relations exist in Hungary and Slovenia. Both are strongly influenced by regulatory patterns formed within the two different communist traditions. Hungarian industrial relations are unitary in nature. They are characterized by trade union integration in managerial structures. At workplace level, Slovenian trade unions are more worker-oriented. In accordance with this basic feature, the whole scene is more pluralistic and more conflicting. Processes of forming industrial relations structures in the two countries are divergent. The divergence is significant, in spite of early implementation of German model in both cases. In both transitional societies the roles of capital and labor differentiate in accordance with the patterns, which are stronger than the imported intermediary institutions. – – Dieser Artikel basiert auf einer Umfrage, die in der zweiten Hälfte des Jahres 1999 durchgeführt wurde. Die Erhebung ergab, dass in Ungarn und in Slowenien zwei verschiedene Arten industrieller Beziehungen existieren, die beide stark von Handlungsmustern reguliert werden, die aus den verschiedenen kommunistischen Traditionen hervorgehen. Industrielle Beziehungen in Ungarn sind einheitlich. Charakteristisch ist die Integration von Gewerkschaften in Managementstrukturen. Auf der Arbeitsplatzebene sind die slowenischen Gewerkschaften stärker arbeiterorientiert. Demzufolge stellen sich die gesamten Beziehungen pluralistischer und konfliktträchtiger dar. Die Entstehungsprozesse der Strukturen industrieller Beziehungen divergieren in beiden Ländern. Die Divergenz ist signifikant, obwohl in beiden Fällen das deutsche Modell frühzeitig implementiert wurde. In beiden Transformationsgesellschaften unterscheiden sich die Rollen von Kapital und Arbeit im Zusammenhang mit diesen Mustern, die sich als stärker erweisen, als importierte zwischengeschaltete Institutionen.
Keywords: 650